On the synonymy of some taxa of the genus Xylena Hübner (Lepidoptera, Noctuidae) - Saldaitis, Aidas; Volynkin, Anton V.; Benedek, Balázs (Zootaxa, 2017)
Xylena czernilai Volynkin, 2011 was described on the base of a single male from the Russian Altai Mts. (Volynkin 2011). Later, two externally similar taxa, Xylena alexander Benedek, Babics & Saldaitis, 2013 and Xylena andreas Benedek, Babics & Saldaitis, 2013 were described from Sichuan province, China each on the base of a single female (Benedek et al. 2013). In the same year, a female of X. czernilai was described by Volynkin & Knyazev (2013). The female genitalia of X. czernilai are surprisingly similar to those of the both Chinese species therefore we decided to use a DNA analysis to clarify the status of these three taxa. For the analysis we sampled a female of X. czernilai from the Russian Altai, a male of X. czernilai from the Russian Far East and the holotypes of X. alexander and X. andreas. The analysis of COI barcodes of the sampled specimens has shown that X. alexander and X. andreas are conspecific (the difference is 0.15 %), and their COI sequences differ from those of X. czernilai in 0.93 % only. Such difference is too small to treat Chinese populations as a distinct species (for example, the difference between X. czernilai and its closest relative X. vetusta (Hübner, [1813]) is 4.61% . The detailed morphological comparison of czernilai and vetusta has been given by Volynkin (2011) (Fig. 1) therefore here we synonymize X. alexander and X. andreas with X. czernilai.